Effects of infrastructures on environmental quality contingent on trade openness and governance dynamics in Africa - Tii Njivukuh Nchofoung; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
The objective of this study is to evaluate: (i) the effects of infrastructures on CO2 emission and (ii) how trade openness and governance contribute to mitigating these effects. The results from the system GMM methodology for 36 African countries between the 2003-2019 period show that infrastructural development exacerbates CO2 emission in Africa. This result is robust across different types of infrastructural development indexes. When the indirect effect regressions are carried out by interacting governance and trade openness with the different infrastructural development variables, the following results are obtained. Firstly, infrastructural development interacts with governance producing a positive net effect, up to a governance threshold estimate of 0.532 when the positive net effect is nullified. Secondly, infrastructures interact with trade openness producing a negative net effect up to a trade openness threshold of 78.066914 (% of GDP) when the negative net effect is nullified. Positive and negative synergy effects are also apparent. Practical policy implications are discussed based on the results obtained.
Keywords: N67; N77; C23; Q56; 330; Infrastructures; CO2; trade openness; governance; Africa; System GMM